Helium-3 - based fusion plasma - Ryzhkov, S.V. (Вопросы атомной науки и техники, 2008)
The experimental devices and conceptual designs of the field-reversed configuration (FRC), tandem mirror and spheromak as best solution for the low radioactive plasma, namely helium-3 based fusion plasma, are reviewed. Reactor schemes based on D-³He-⁶Li fuel with the possibility of ³He mining on the Earth and Moon, including breeding and support reactors are proposed. 3He acquisition, some estimation and resources are presented. Applications of D-³He reactions and advanced-fueled alternative systems are discussed.